Identifying Elementary Students Collaboration Skill through the Daily Class Picket - Maulana, Angga; Sa'ud, Udin Saefudin (International Conference on Elementary Education, 2022)
Collaborative skills have an important role in facing the challenges of the 21st century. Collaborative skills can be instilled in learning as well as with school culture through example and habituation. This study aims to determine the collaboration skills of students through daily class picket activities. This study uses a qualitative approach. Data collection techniques using observation. The research results are presented descriptively. The results show that students are very good at collaborating (95%), able to actively contribute very well (90%), able to work productively very well (92%), able to perform roles flexibly, and able to compromise well (91% ), responsible for the task very well (98%), can appreciate friends very well (96%). This study illustrates that daily class picket activities can be a strategic choice to train and grow students' collaboration skills other than through learning.